PENINGKATAN PEMAHAMAN KONSEP MATEMATIKA MELALUI MEDIA VISUAL PADA SISWA KELAS IV SD NEGERI WIDORO - Novy Trisnani; Wulan Tri Puji Utami (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2020)
This study aims to improve the ability to understand the concept of the properties of the flat figure of fourth grade students of SD Negeri Widoro through visual learning media. This type of research is classroom action research. The subjects in this study were grade IV students of SD Negeri Widoro as many as 30 students. Data collection techniques using tests, observations, and documentation. The instrument used in the form of learning achievement tests, concept understanding tests, and observation sheets. Data analysis techniques using qualitative and quantitative. The results of observation before the action showed that the average comprehension ability of students 'mathematical concepts was 65.67, which was included in the sufficient category. Then in the first cycle, the ability to understand students' mathematical concepts on average increased from the low to the high categories (understanding ability average concept of 74.48. To strengthen the observations of the first cycle, learning activities continued with the second cycle, the results of understanding the ability of mathematical concepts increased from 74.48 to 84.53 in the high category, while students' learning completeness in the first cycle was 73.33 in cycle II increased to 76.67 and has met the minimum completeness criteria in the material properties of flat shape. Based on the results of the research it can be concluded that the use of visual learning media can improve the understanding of mathematical concepts of fourth grade students of SD Negeri Widoro in the school year 2019/2020.